PERANCANGAN SISTEM INFORMASI MANAJEMEN KEGIATAN MAHASISWA BERBASIS WEB - Ana Juita Oktasari; Denny Kurniadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This article discusses about management of student activities in the process of submitting activity proposals, reviewing and reporting activities. Carried out by student activity units at the State University of Padang  which aims to minimize the time, energy and cost of implementing procedures for submitting proposals and reporting activities. In meeting Head of Students Affairs, WR III (interest and talent section) and KaBag (treasurer section). Submission of proposals and activity reports should be in accordance with technological developments at this time to effective and efficient. In designing this information system using the method waterfall method and the Object Oriented Programming (OOP) method. This system also uses the Model View Controller (MVC) technique. This system is design usimg Yii2 Framework with the Hypertext Preprocessor (PHP) and MySQL Database Management System (DBMS) programming languages. Designing a student activity management information system produces a system that can facilitate student activity units at State University of Padang in submitting proposals and activity reports and assisting the Head of Student Affairs in managing information about students activities. Keywords:Information Systems, College Student Activity, SQL, MVC, Framework Yii2.